Serum Magnesium and Cognitive Function Among Qatari Adults - Al-Ghazali, Kateba; Eltayeb, Sana; Musleh, Ayesha; Al-Abdi, Tamara; Ganji, Vijay; Shi, Zumin (Frontiers in Aging Neuroscience, 2020)
Background: Previous studies found that low blood magnesium increase the risk of several diseases such as cardiovascular diseases, diabetes, and hypertension. These ailments are associated with declined cognitive function. Objective: We aimed to examine the association between serum magnesium and cognitive function among Qatari adults. In addition to assessing the interaction relation between low serum magnesium, hypertension, and diabetes in relation to cognitive function. Method: Data from 1000 Qatari participants aged ≥20 years old who participated in the Qatar Biobank Study were analyzed. Serum magnesium was measured by an automated calorimetric method and suboptimal magnesium was characterized by <0.85 mmol/L. Cognitive function was determined by measuring mean reaction time (MRT) based on a computer-based self-administered test. Multivariable linear regression was used to examine the relation between serum magnesium concentrations and cognitive function. Results: The prevalence of suboptimal magnesium was 57.1%. Across the quartiles of serum magnesium, the regression coefficients (95% CI) for MRT were 0 (reference), -17.8, -18.3, and -31.9 (95%CI 2.4–3.1), respectively (p for trend 0.05). The presence of hypertension and diabetes significantly increased the MRT. Women with suboptimal magnesium and hypertension had the highest MRT. Conclusion: The prevalence of suboptimal magnesium is high. There was a positive association between serum magnesium and cognitive function. Low magnesium levels were associated with a longer MRT.